EMERGING CHALLENGES IN ORGANIZED CRIME - B. Gaikwad, Anil; Anjum, Talat; Rishi, Animesh (International Journal of Psychosocial Rehabilitation, 2020)
The European Union's and Lithuania's attitudes on organized crime are compared in this study. It is hoped that it would have a positive impact on the economy and society. On the basis of this research, the author examined European Union and national strategic documents identifying the threats of organized criminality; he also assessed organized crime groups, their spheres of activity, their impact on social security, and factors that determine the peculiarities of organized criminality's development. For the purposes outlined in this article, organized crime is being examined in terms of its threat to national security, as well as its structure, activities, so-called "engines," and the main "crime enabler" factors that influence the evolution of criminality; and 3) to assess new threats and propose specific measures to combat organized crime as an issue. Analysis of legal precedents and documents is among the tools used by the author. Interviews with civil servants and operational officers yielded additional material, which is also included in the report.